2019
DOI: 10.1136/archdischild-2019-317117
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and clinicians’ views on conducting paediatric diagnostic test accuracy studies without prior informed consent: qualitative insight from the Petechiae in Children study (PiC)

Abstract: ObjectiveThe Petechiae in Children (PiC) study assesses the utility of presenting features and rapid diagnostic tests in the diagnosis of serious bacterial infection in feverish children with non-blanching rashes. An embedded qualitative study explored parents’ and clinicians’ views on the acceptability of the PiC study, including the use of research without prior consent (RWPC) in studies of diagnostic test accuracy.DesignSemistructured qualitative interviews. Analysis was thematic and broadly interpretive, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Due to the potentially life-threatening nature of invasive MD, research without prior consent (RWPC) was utlilised, and is described in full in the published study protocol (14,16,17).…”
Section: Consent Modelmentioning
confidence: 99%
“…Due to the potentially life-threatening nature of invasive MD, research without prior consent (RWPC) was utlilised, and is described in full in the published study protocol (14,16,17).…”
Section: Consent Modelmentioning
confidence: 99%
“…For this study, we will use research without prior consent (RWPC) methodology 17 18. This approach has been shown to be effective and acceptable to both parents and clinicians for diagnostic studies based on prior works such as the Petechiae in Children Study 19 20. RWPC has also been used in the EcLiPSE trial undertaken by PERUKI 21.…”
Section: Methodsmentioning
confidence: 99%
“…The literature describes parental support for the concept of deferred consent in paediatric emergency and/or critical care research, depending on the nature of the trial 8,9,11,14,19 . One study surveyed the level of support for deferred consent and found 91% of parents were satisfied with the consent process 20 .…”
Section: Does the National Statement Align With Patient Parent And Pr...mentioning
confidence: 99%